Estudo comparativo da injeção de água usando poços verticais e horizontais - Ruiz, Cindy Pamela Aguirre (2012)
Oil recovery using waterflooding has been until now the worldwide most applied method, specially for light oil recovery, its success is mainly because of the low costs involved and the facilities of the injection process. The Toe- To-Heel Waterflooding TTHWTM method uses a well pattern of vertical injector wells completed at the bottom of the reservoir and horizontal producer wells completed at the top of it. The main producing mechanism is gravitational segregation in short distance. This method has been studied since the early 90´s and it had been applied in Canada with positive results for light heavy oils, nevertheless it hasn´t been used in Brazil yet. In order to verify the applicability of the process in Brazil, a simulation study for light oil was performed using Brazilian northwest reservoirs characteristics. The simulations were fulfilled using the STARS module of the Computer Modelling Group Software, used to perform improved oil recovery studies. The results obtained in this research showed that the TTHWTM well pattern presented a light improvement in terms of recovery factor when compared to the conventional 5- Spot pattern, however, it showed lower results in the economic evaluation